Glypican-3 is a key tuner of the Hedgehog pathway in COPD - Laure M.G. Petit; Lynda Saber Cherif; Maëva A. Devilliers; Sarah Hatoum; Julien Ancel; Gonzague Delepine; Anne Durlach; Xavier Dubernard; Jean-Claude Mérol; Christophe Ruaux; Myriam Polette; Gaëtan Deslée; et al. (Heliyon, 2025)
Hedgehog (HH) pathway is involved in pulmonary development and lung homeostasis. It orchestrates airway epithelial cell (AEC) differentiation and contributes to respiratory pathogenesis. The core elements Gli2, Smo, and Shh were found altered in the bronchial epithelium of patients with chronic obstructive pulmonary disease (COPD). Here, we investigated the co-receptors to fully decipher the complex machinery of airway HH pathway activation in health and COPD. The core elements and co-receptors of HH signalling were investigated in lung cell populations using single-cell RNAseq analysis. The transcript levels of the principal co-receptor GPC3 were investigated on public RNAseq datasets and by RT-qPCR. The localisation of GPC3 was evaluated through immunofluorescent stainings on isolated bronchial AEC and tissues from non-COPD and COPD patients. GPC3 pharmacological modulation was achieved with Codrituzumab during AEC differentiation. We demonstrated that the core elements were not abundant in pulmonary cell populations. Focusing on co-receptors, GPC3 was the most expressed transcript in tracheobronchial epithelial cells. The decrease in GPC3 transcript levels correlated with the severity of airway obstrution in COPD patients. Finally, interfering with GPC3 signalling during AEC differentiation induced downregulation of the HH pathway attested by a decrease of Gli2 leading to reduced ciliogenesis and altered mucin production. GPC3 appears as a crucial co-receptor for the HH pathway in the respiratory context. The modulation of GPC3 may represent a novel experimental strategy to tune HH signalling in therapeutic perspectives.